Use of Decompression and Transpedicle Fixation in the Patients of Thoracic Spine Tuberculosis - Naeem Ul Haq, Abdus Samad Khan, Hamid Ullah, Abdul Jalal (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Posterio-lateral decompression and transpedicle fixation for TB of the thoracic spine are the focus of the present study. Study Design: Cross-sectional/observational study Place and Duration: The study was conducted at the department of Neurosurgery, Mardan Medical Complex for duration of four years from July 2017 to June 2021. Methods: Total 18 patients of both genders with ages 18-65 years were included. Case demographics, such as age, gender and BMI, were gathered after obtaining written permission from all participants. Included patients were undergone posterio-lateral decompression and trans-pedicle fixation for thoracic spine tuberculosis. Post-operative outcomes among all patients were recorded in terms of reduction of pain score by VAS, improvement in neurological deficit and frequency of complications. All the data was analyzed by using the SPSS 20.0 version. Results: Among 18 cases, there were 12 (66.7%) males and 6 (33.3%) females with mean age 35.8± 8.51 years and had mean BMI 24.6±5.51 kg/m2. Post-operative improvement in the reduction of pain score was noted among 15 (83.3%) cases. According to ASIA score improvement in neurological deficit was recorded among 14 (77.8%) patients. Frequency of complications was 1 (5.5%). Conclusion: According to this research, it is safe to do posterior-lateral decompression and trans-pedicle fixation for TB of the thoracic spine. It is effective in relieving pain and improving neurological function. Complications are rare after this treatment. Because of this, it is a viable alternative to conventional surgical methods for the treatment of TB of the thoracic spine.